Cryptic speciation of benthic Prorocentrum (Dinophyceae) species and their potential as ecological indicators - Yixuan, Wu; Shuning, Huang; Bernd, Krock; Chui, Pin Leaw; Teng, Sing Tung; Ajcharaporn, Piumsomboon; Kakaskasen, Andreas Roeroe; Na, Wang; Haifeng, Gu (Elsevier B.V, 2022)
The response of marine ecosystems to rapid climate changes has been well recognized but not studied extensively. Benthic microalgae, in contrast to the phytoplankton that is able to be transported by currents, have limited dispersal ability and thus are a better ecological indicator to climate changes. Here we performed sampling in the Yellow Sea, the East China Sea and South China Sea and established twenty-six strains of benthic Prorocentrum for detailed morphological and molecular examinations. Five Prorocentrum species, including P. concavum, P. fukuyoi, P. mexicanum, P. tsawwassenense, and P. cf. sculptile, were identified. Both P. concavum and P. fukuyoi displayed marked intraspecific divergences in large subunit (LSU) ribosomal RNA gene sequences, corresponding to their geographical origins. In contrast, P. mexicanum strains shared identical LSU sequence. Prorocentrum tsawwassenense and P. cf. sculptile are not suitable ecological indicators as they were rarely observed. Prorocentrum mexicanum is not recommended either as it is present across the region. In contrast, P. concavum and P. fukuyoi have advantages as ecological indicators for climate changes in the Western Pacific as they comprise several ribotypes with differentiated biogeography. Toxin analysis was also performed on all five species except P. fukuyoi by liquid chromatography coupled to tandem mass spectrometry, but okadaic acid was not detectable.